The Effect of Audit Quality, Profitability, Liquidity, and Solvency on Going Concern Audit Opinions in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2020-2023 - Andalas, Ricgo Putra; Friyani, Rita; Erawati, Misni (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study was conducted with the aim of obtaining information on the effect of Audit Quality, Profitability, Liquidity, and Solvency on going concern audit opinion. The population used during this study were companies engaged in the property and real estate sector listed on the Indonesia Stock Exchange for the period 2020-2023. The sample in this study was selected using purposive sampling method with the number obtained as many as 284 samples. This study uses logistic regression analysis method. The results obtained provide information that profitability has a significant negative effect on business continuity opinion. Then auditor quality, liquidity, and solvency have no significant effect on business continuity opinion. Simultaneously audit quality, profitability, liquidity, and solvency have an influence on business continuity opinion.